2016
DOI: 10.2139/ssrn.2725980
|View full text |Cite
|
Sign up to set email alerts
|

Coco Design, Risk Shifting and Financial Fragility

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…But the risk shifting incentives induced by CoCos may result in upward pressure on probability of default (Koziol and Lawrenz (2012), Hilscher and Raviv (2014), Berg and Kaserer (2015), Chan and van Wijnbergen (2017), Goncharenko (2017)). …”
Section: Introductionmentioning
confidence: 99%
“…But the risk shifting incentives induced by CoCos may result in upward pressure on probability of default (Koziol and Lawrenz (2012), Hilscher and Raviv (2014), Berg and Kaserer (2015), Chan and van Wijnbergen (2017), Goncharenko (2017)). …”
Section: Introductionmentioning
confidence: 99%
“…The lines for different leverage converge to the same point on the vertical axis as ∆ → 0; for a PWD CoCo, leverage has no impact on the price since both the CoCo and equity are junior to debt. This result does depend on the assumption that the variance of the asset value process is exogenously chosen; if it would be endogenously chosen, higher leverage would lead to more risk taking and a higher variance, which would have an impact on the value of the CoCo even if it has a PWD structure (this point is made in Chan and van Wijnbergen (2016;revised November 2017)). 6.4 Capital structure, CoCos and Risk Taking Incentives…”
Section: On Dilution and Leveragementioning
confidence: 99%
“…Despite this, 60 percent of the recently issued CoCos is of the principal write down (PWD) type, where instead of being converted to equity, CoCos are written down with a pre-defined percentage. In Chan and van Wijnbergen (2015) and Chan and van Wijnbergen (2016) it is argued that this feature is highly undesirable, as it could increase the systemic risk and give equity holders an incentive to increase the risk taken instead of decreasing it. Despite this, the opposite effect can occur as well, as described in Martinova and Perotti (2015), where it is shown that under certain assumptions the risk-taking incentive is higher with CE as compared to PWD Cocos.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This design resolves the multiple equilibria or no equilibrium problem, from now on referred to as the multiple equilibria problem (see Sundaresan and Wang (2015)). This design could, furthermore, reduce the potential increasing risk-taking incentives addressed in Berg and Kaserer (2015) and Chan and van Wijnbergen (2016) and the problems with pricing Co-Cos due to the hybrid structure as in Wilkens and Bethke (2014). The lack of a unique equilibrium price for the CoCos and equity could cause high volatility in these prices and lead to discomfort among investors.…”
Section: Introductionmentioning
confidence: 99%